2017
DOI: 10.1016/j.celrep.2017.03.050
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Regulates Stress Responses through HDAC2

Abstract: Stress causes changes in neurotransmission in the brain, thereby influencing stress-induced behaviors. However, it is unclear how neurotransmission systems orchestrate stress responses at the molecular and cellular levels. Transient receptor potential vanilloid 1 (TRPV1), a non-selective cation channel involved mainly in pain sensation, affects mood and neuroplasticity in the brain, where its role is poorly understood. Here, we show that Trpv1-deficient (Trpv1) mice are more stress resilient than control mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 45 publications
1
45
1
1
Order By: Relevance
“…There are a number of reports of the functional roles of HDAC2 in the maturation of neural cells, 26 , 27 especially in neurogenesis 28 and synaptic plasticity. 17 According to our recent work, 7 TRPV1 loss of function induces downregulation of HDAC2 in the DG, leading to elevated expression of neurogenesis- and synaptic plasticity-related genes, which contributes to stress-resilient behavior. However, increase of HDAC2 expression in the DG induces depression-like behaviors, which were blocked by HDAC2 knockdown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a number of reports of the functional roles of HDAC2 in the maturation of neural cells, 26 , 27 especially in neurogenesis 28 and synaptic plasticity. 17 According to our recent work, 7 TRPV1 loss of function induces downregulation of HDAC2 in the DG, leading to elevated expression of neurogenesis- and synaptic plasticity-related genes, which contributes to stress-resilient behavior. However, increase of HDAC2 expression in the DG induces depression-like behaviors, which were blocked by HDAC2 knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV1 activation by systemic injection of agonists such as capsaicin and resiniferatoxin elicits anxiogenic responses and depression-related behaviors, whereas its antagonists induce anxiolytic- and antidepressant-like effects in rodents. 4 , 5 , 6 , 7 Besides, direct injection of capsaicin or capsazepine in the hippocampus induces anxiety- or anxiolytic-like effects. 8 , 9 These effects are accompanied by impaired hippocampal neurogenesis through epigenetic regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following single injections of various doses of metformin, the anti-depressant effect was indicated by the responses in the forced swimming test (FST) and tail suspension test (TST), two widely used behavioral tests of depression. The FST focuses immobility time after mice being placed in a tank filled with water from which animals cannot escape, while the TST has a common theoretical basis and behavioral measure with the FST but avoids motor dysfunction that may interfere with evaluation in a FST [36,37]. In the group that received metformin > 10 mg/kg, the immobility time in the FST and TST was significantly decreased compared to that in the vehicle-injected or 10 mg/kg metformin-injected groups (F (4, 35) = 6.226, P < 0.001 for FST; F (4, 35) = 9.961, P < 0.001 for TST; Fig.…”
Section: Metformin Exerts Antidepressant Effects On Mice In a Dose-anmentioning
confidence: 99%
“…TRPV1 channel belongs to the Ca 2+ permeable TRPV channel family, responding to noxious heat (>43℃), low pH value (<5), capsaicin and so on [10][11][12]. TRPV1 channel plays an important role in several physiological and pathological processes, such as nerve conduction, visceral pain sensing process [9,13,14], and activation of immunity [15]. Furthermore, a few studies shown previously that TRPV1 was likely involved in tumor progression [16], and its activation reduced cell proliferation, migration and invasion in breast cancer [17], urothelial cancer [18] and papillary thyroid carcinoma [19].…”
Section: Introductionmentioning
confidence: 99%